Peran Adopsi Digital Banking dalam Memediasi Pengaruh Literasi Keuangan dan Literasi Digital Terhadap Financial Inclusion pada Nasabah Bank 9 Jambi - Sefnilia Munawaroh; Rike Setiawati; Besse Wediawati (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of financial literacy and digital literacy on financial inclusion and examine the role of digital banking adoption as an intervening variable among customers of the Jambi Regional Development Bank. The study employed a quantitative approach with an explanatory research design. Primary data were collected through the distribution of Likert-scale questionnaires to customers of the Jambi Regional Development Bank selected as research respondents. Data analysis was performed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of the SmartPLS application. The analysis stages included testing the outer model to assess the validity and reliability of the instrument, testing the inner model to examine the relationship between variables, and analyzing the mediating effect of digital banking adoption. The results showed that financial literacy and digital literacy positively influenced the adoption of digital banking. In addition, digital banking adoption positively influenced financial inclusion and was able to mediate the influence of financial literacy and digital literacy on financial inclusion. These findings indicate that improving financial literacy and digital literacy needs to be accompanied by optimizing the use of digital banking services to expand public access to formal financial services.